2015
DOI: 10.1111/ahe.12177
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Age‐related Changes of Peripheral Nerves in Cattle: Morphological and Biochemical Studies

Abstract: Peripheral nerve function is significantly affected by ageing. During ageing process, multiple changes occur on tissue cells and extracellular matrix. The aim of this work was to study the ageing-associated changes of peripheral nerves in adult and old regularly slaughtered cattle compared with young calves, and correlate them to the features reported in humans and laboratory animals. Samples of axial dorsal metacarpal nerves from 44 cows were collected immediately after slaughtering. Each nerve was dissected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…On the other hand, Biasibetti et al reported that decreased angiogenesis, a decrease in nerve fibers, and myelin degeneration are age-associated changes in peripheral nerves (5). Furthermore, we previously reported a mechanism to prevent oxidative stress-induced peripheral nerve degeneration (6).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…On the other hand, Biasibetti et al reported that decreased angiogenesis, a decrease in nerve fibers, and myelin degeneration are age-associated changes in peripheral nerves (5). Furthermore, we previously reported a mechanism to prevent oxidative stress-induced peripheral nerve degeneration (6).…”
Section: Introductionmentioning
confidence: 69%
“…Verdú et al reported that Schwann cell function declines due to aging, delaying Waller degeneration and axon regeneration after peripheral nerve damage (10). In addition, the vascular regeneration ability of nerve tissue after peripheral nerve damage was recently demonstrated to decrease with age (5,11). On the other hand, the generation of new blood vessels starting from the proximal nerve stump after peripheral nerved damage is important (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have targeted ECM remodeling as a promising therapeutic approach to wound repair and regeneration [16]. However, there are only a few reports dealing with the morphological changes within the endoneurium of the peripheral nerve associated with aging, and these findings have been obtained in animals [3,4,[17][18][19][20][21][22]. To the best of our knowledge, there are no papers dealing with quantitative age-related changes of the components of the ECM in the endoneurium of the human peripheral nerve.…”
Section: Morphometric Analysis Of the Human Endoneurial Extracellularmentioning
confidence: 99%
“…The acidic mucopolysaccharides that accumulated in the peripheral nerves of the BEFVinfected animals along with the paucity of myelin staining within the degenerate nerve tissue may suggest that formation of mucopolysaccharide-rich intermediates derived from the breakdown of myelin-sheath-associated-proteins occurred in these animals (Meir and Bischoff, 1977). On the other hand, Biasibetti et al (2016) have reported age-related axonal degeneration and demyelination in bovine peripheral nerves derived from 10-20-year-old cattle but not in 12-29-months-old animals used as the negative control. Since the cattle used in the present study had a mean age of about 2-years-old, age-related peripheral neuropathy is unlikely.…”
Section: Discussionmentioning
confidence: 98%